Diabetes awareness education for teenagers at Manba'ul 'Ulum Vocational School, Cirebon Regency - Yayan Rizikiyan; Tomi Tomi; Addelya Regina Oktaviani; Yasa Julio; Hajray Adhanisa Santysharma; Naftaly Ninda; Dhea Nasyandha Aryanty; Monthery Bryan Bagaskara; Eka Pratiwi; Siti Silfa Alfiah; Cindy Amalia Ramdhani; Vania Carlita Putri; Alifia Hasna (Universitas Muhammadiyah Magelang, 2024)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Diabetes prevention is carried out through early disease detection and appropriate lifestyle management, primarily in dietary regulation. This community service activity aims to educate students of SMK Manba'ul 'Ulum, Cirebon Regency, about diabetes, including its characteristics, prevention, and treatment. The method used in this activity is education through counseling, accompanied by pre-tests and post-tests. Education is also carried out by distributing leaflets about diabetes. The results of the pre-test and post-test showed an increase in participants' understanding of diabetes from 73% to 94%.